Kinetics of antibody-secreting cell and fecal IgA responses after oral cholera vaccination in different age groups in a cholera endemic country. Issue 2 (5th January 2017) - Akhtar, Marjahan; Qadri, Firdausi; Bhuiyan, Taufiqur R.; Akter, Sarmin; Rafique, Tanzeem A.; Khan, Arifuzzaman; Islam, Laila N.; Saha, Amit; Svennerholm, Ann-Mari; Lundgren, Anna
Highlights: Bangladeshi infants, children and adults received two oral cholera vaccine doses. ASC responses to the second dose were induced earlier than previously appreciated. Fecal SIgA responses developed later than ASC responses in young children/infants. The results have implications for the sampling schedule in oral vaccine trials. Abstract: Immune responses to oral enteric vaccines in children and infants may be influenced by factors such as age, previous priming with related microorganisms and breast feeding. In this study, we aimed to determine optimal time points to assess immune responses to oral enteric vaccines in different clinical specimens. This was done by investigating antibody secreting cell (ASC) and fecal antibody responses on different days after vaccination using the licensed oral cholera vaccine Dukoral, containing cholera toxin B-subunit (rCTB) and inactivated Vibrio cholerae bacteria, as a model vaccine. Two vaccine doses were given 2 weeks apart to infants (6–11 months), young children (12–18 months), toddlers (19 months–5 years) and adults in a cholera endemic country (Bangladesh). IgA ASC responses, as determined by the antibodies in lymphocyte supernatant (ALS) assay, plasma IgA and IgG responses and secretory IgA (SIgA) responses in extracts of fecal samples were evaluated 4/5 and 7 days after each vaccination. After the first vaccine dose, anti-CTB ALS IgA responses in adults and toddlers were high and comparable on day 5 and 7, while responses were low and infrequent in young children. After the second dose, highest ALS responses were detected on day 5 among the time points studied in all age groups and the responses declined until day 7. In contrast, plasma IgA and IgG anti-CTB responses were high both on day 5 and 7 after the second dose. Fecal SIgA responses in young children and infants were highest on day 7 after the second dose. Our results suggest that ASC/ALS responses to two doses of the oral cholera vaccine Dukoral and related oral vaccines should be analyzed earlier than previously recommended (day 7) at all ages. Fecal antibody responses should preferably be analyzed later than ASC/ALS responses to detect the highest antibody responses.